2017
DOI: 10.1007/s12975-017-0541-7
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-7 Nicotinic Receptor Signaling Pathway Participates in the Neurogenesis Induced by ChAT-Positive Neurons in the Subventricular Zone

Abstract: Choline acetyltransferase-positive (ChAT+) neurons within the subventricular zone (SVZ) have been shown to promote neurogenesis after stroke in mice by secreting acetylcholine (ACh); however, the mechanisms remain unclear. Receptors known to bind ACh include the nicotinic ACh receptors (nAChRs), which are present in the SVZ and have been shown to be important for cell proliferation, differentiation, and survival. In this study, we investigated the neurogenic role of the α7 nAChR in a mouse model of middle cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…) and ischemic stroke (Wang et al . ). Importantly, previous studies have shown that administration of α7nAChR agonists to humans is well tolerated (Deutsch et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and ischemic stroke (Wang et al . ). Importantly, previous studies have shown that administration of α7nAChR agonists to humans is well tolerated (Deutsch et al .…”
Section: Discussionmentioning
confidence: 97%
“…), neurogenesis (Wang et al . ), and by activating neuroprotective signaling pathways (Dajas‐Bailador et al . ; Kihara et al .…”
mentioning
confidence: 99%
“…We sacrificed the mice on days 1 and 3 after tMCAO to determine the brain water content as previously described [ 30 , 37 ]. The brain was divided into two hemispheres from the anatomic midline.…”
Section: Methodsmentioning
confidence: 99%
“…We sacrificed mice on day 3 after surgery for immunofluorescence analysis as previously described [ 30 , 31 , 39 ]. Briefly, mice were anesthetized with an intraperitoneal injection of 5% chloral hydrate and perfused with PBS and 4% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, nicotine can protect cells against apoptosis through the upregulation of XIAP and survivin in a α3-nAChR-dependent manner (Dasgupta et al, 2006). Overall it appears that the cell proliferation and differentiation during development are mostly mediated by α7 nAChR and pro-survival effects are mediated by α3 or α4 nAChR (Dasgupta et al, 2006; Resende et al, 2008; 2008 a; Wang et al, 2017; West et al, 2003). These findings support our results indicating nicotine provides neuroprotection through both α3 and α7 nAChRs with a greater role for α3 nAChRs in preventing apoptosis upon NGF withdrawal in SCG neurons.…”
Section: Discussionmentioning
confidence: 99%